Q11 Huntington's disease Italian trial in neuro-transplantation: update on 17 patients group. (29th August 2012) - Ghelli, E; Pradella, S; Romoli, AM; Fortunato, F; Paganini, M; Gallina, P; Vannelli, G; Piacentini, S; Di Lorenzo, N; Sorbi, S
Abstract : Introduction: Embryonic striatal cells grafts transplanted into rat striatum have been shown to be effective in reversing behavioural deficits, including motor and cognitive impairments in Huntington's disease (HD) rat models. For this reason, neuroblast transplantation has been recently explored as therapeutic chance in HD. In our series, we performed, during the last 7 years, human foetal striatum transplantations (HFST) in 17 patients, according to the protocol previously reported. Main results are shown. Methods: Standard procedure was applied to the first six transplantation surgeries, the remaining grafts were performed by a double approach refinement. Sixteen HD patients were enrolled in the control group. Patients underwent Unified HD Rating Scale (UHDRS), neuropsychological, psychiatric battery, regular MRI and 18F-FDG PET exams. Results: Seventeen patients underwent procedures bilaterally, follow-up ranged between 11 months and 6 years. Gender ratio of the patients was 5F/12M, mean age was 51 yrs (±8.17 DS), the age at disease onset was 37.4 yrs (±9.6 DS), mean duration of illness 12.6 yrs (±4.6 DS), mean CAG repeats 48 (±5.14 DS). Demographic, genetic and clinical features of the control group were comparable to those of the grafted patients. If we compare patients before and after transplantation the progression of motor symptoms was slower after grafting. Most of our patients showed an improvement of the choreic movements within the first week, maybe due a possible corticothalamic tractotomy. At 2 years follow-up, [18F]FDG PET showed cortical/striatal metabolic improvement. At the 4 years follow-up in 8 patients, despite reduction, metabolism remained higher than at baseline, particularly in striata. Conclusions: HFST was feasible and safe. The efficacy of HFST is still under debate. Comparing animal studies with our series and previously reported, it's worth noting a similar metabolic increase, that did not correspond to similar results in behaviour/clinical picture. More studies are necessary to assess functional connection with host structure, to understand and promote graft retraining in the striatum and to evaluate clinical efficacy of the human fetal striatal transplantation.